(untitled) (Scientific journal of the Fergana State University, 2024)
In the modern world, digital technologies have become an integral part of our lives. They penetrate into all areas of activity, including education. The author of the article considers the use of digital technologies in the field of humanities education as the goal of the study, when discussing the prospects for cooperation and innovation. And in connection with this situation, it is important to continue research in this area in order to find the best ways to use digital technologies to improve the quality of humanities education.